(untitled) (Singaporean Journal of Business Economics and Management, 2015)
In order that culture and organisation is more competitive and effective in the business environment, it is imperative that departments within the same organisation align themselves with the organisation’s values and vision. During a merger or acquisition different departments bring along with them assumptions which may thwart the overall effectiveness of the organization. Therefore, it is necessary that proper socialisation and induction becomes an important and cardinal facet of the organization, in order to ensure that the different cultures are dissolve during a merger. The aim of this study was to determine the impact the cultural differences of the merged departments, (Department of Customs and Domestic Taxes) on the strategy and overall effectiveness of the Swaziland Revenue Authority (SRA) as it undertakes its mandate. Various factors influencing the culture of the departments had been identified in this study and how each element of culture impacts on the effectiveness of the organization.